Sealing rubber strip, preparation method of sealing rubber strip and application of sealing rubber strip in vacuum forming of composite material
By optimizing the raw materials and processes of sealant strips, improving their crosslinking degree and pore filling effect, the problem of insufficient high temperature and high pressure resistance in vacuum forming of composite materials is solved, and efficient airtightness and easy removal are achieved.
Patent Information
- Application Number
- CN202411819248.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-14
AI Technical Summary
During the vacuum forming process of composite materials, the sealant strips need to withstand high temperature and high pressure. The pressure resistance of the existing sealant strips is insufficient, making it difficult to meet the continuously improved product quality requirements.
The sealant strip is made of raw materials such as synthetic rubber, natural rubber, Gumalon resin, phenolic resin, filler, POSS modified glass microspheres, expandable microspheres, tackifiers, zinc oxide, stearic acid, toner and anti-aging agents, and the crosslinking degree and pore filling effect of the rubber strips are improved through specific kneading and molding processes.
The shape retention ability of the sealant strip under high temperature and high pressure is achieved, ensuring airtightness, and can be easily removed after use, meeting the performance requirements of vacuum forming of composite materials.
Smart Images

Figure CN119613878A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional materials, and in particular relates to a sealing strip and a preparation method thereof and application thereof in vacuum forming of composite materials. Background Art
[0002] Resin-based composite materials are widely used in aerospace, rail transit, wind power and shipbuilding and other fields. Their molding mainly adopts the autoclave molding process. During the curing molding process of the resin prepreg autoclave, the vacuum bag and the mold need to be sealed while evacuating the vacuum, which requires the combination of materials with good sealing properties.
[0003] The resin matrix of resin-based composite materials is generally epoxy resin, bismaleimide resin, cyanate resin or phenolic resin. During the molding process of resin prepreg, a certain temperature and external pressure need to be maintained. By applying external pressure, the gap between the layers of the resin prepreg can be made smaller and the fit more closely. The external pressure currently applied is generally 0.7MPa.
[0004] However, with the continuous improvement in the quality requirements for composite materials, the external pressure applied has gradually increased to 2MPa, which puts more stringent requirements on the pressure resistance of the sealing strips that perform sealing functions. Summary of the invention
[0005] The purpose of the present invention is to provide a sealing strip and a preparation method thereof and application in composite material vacuum forming. The sealing strip provided by the present invention is resistant to high temperature and high pressure.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] The invention provides a sealing rubber strip, which is prepared from the following raw materials in parts by weight: 60-80 parts of synthetic rubber, 15-20 parts of natural rubber, 5-7 parts of coumarone resin, 5-15 parts of phenolic resin, 50-80 parts of filler, 1-5 parts of POSS modified glass microspheres, 1-5 parts of expandable microspheres, 10-50 parts of tackifiers, 1-10 parts of zinc oxide, 0.5-5 parts of stearic acid, 0.1-5 parts of color powder and 0.1-2 parts of antioxidant.
[0008] Preferably, the synthetic rubber includes one or more of butyl rubber, chlorinated butyl rubber, brominated butyl rubber, nitrile rubber, chloroprene rubber, ethylene propylene rubber and ethylene propylene diene monomer rubber.
[0009] Preferably, the particle size of the filler is 400-1000 mesh.
[0010] Preferably, the POSS modified glass microspheres are POSS modified hollow glass microspheres; the particle size of the POSS modified glass microspheres is no more than 30 μm, and the wall thickness is 1.5 to 3.5 μm.
[0011] Preferably, the expandable microspheres include one or more of thermoplastic polyurethane, thermoplastic rubber and polyvinyl chloride.
[0012] Preferably, the antioxidant includes one or more of an amine antioxidant, a phenol antioxidant and an organic sulfide antioxidant.
[0013] The present invention also provides a method for preparing the sealing strip described in the above scheme, comprising the following steps:
[0014] (1) Plasticizing synthetic rubber and natural rubber and then discharging them to obtain premixed rubber;
[0015] (2) The premixed rubber is mixed with coumarone resin, phenolic resin, filler, POSS modified glass microspheres, expandable microspheres, tackifier, zinc oxide, stearic acid, toner and antioxidant in sequence, allowed to stand and extruded to obtain the sealing strip.
[0016] Preferably, the preparation method of the POSS modified glass microspheres is: glass microspheres, alkali and water are mixed to carry out hydroxylation reaction to obtain hydroxylated glass microspheres, the hydroxylated glass microspheres are mixed with alcohol and a coupling agent to carry out thiol reaction to obtain thiolated glass microspheres, and the thiolated glass microspheres are mixed with vinyl-cage polysilsesquioxane, a photoinitiator and tetrahydrofuran to carry out ultraviolet light reaction.
[0017] Preferably, the temperature of the plasticizing is 30-50° C., the roller distance is 50-800 μm, and the speed ratio is 1:1.2-1.3; and the plasticizing is stopped after 10 thin passes.
[0018] The present invention also provides the use of the sealing strip described in the above scheme or the sealing strip obtained by the preparation method described in the above scheme in vacuum forming of composite materials.
[0019] The present invention provides a sealing rubber strip. The sealing rubber strip provided by the present invention can withstand high temperature and high pressure at the same time, has good air tightness, and can be removed after use. The present invention optimizes the raw materials, utilizes the characteristic that the volume of expandable microspheres increases at high temperatures, increases the pressure resistance of the sealing rubber strip, uses POSS-modified glass microspheres as an auxiliary agent, increases the cross-linking degree of the three-dimensional network of the rubber, and the glass microspheres also effectively fill the pores, and also have a supporting effect on the expanded microspheres, further stabilizes the size of the sealing rubber strip, thereby ensuring the sealing performance under high temperature and high pressure.
[0020] The present invention also provides a method for preparing the sealing strip described in the above scheme. The preparation method provided by the present invention has simple steps, convenient operation, high product reliability, high feasibility, and meets the requirements of industrial production. The sealing strip prepared by the present invention is resistant to high temperature and high pressure, can withstand a high temperature of 230°C without decomposition, and ensures airtightness under an external pressure of 2MPa, and can be easily removed from the mold surface after use.
[0021] The present invention also provides the use of the sealing strip described in the above scheme or the sealing strip obtained by the preparation method described in the above scheme in vacuum forming of composite materials. The sealing strip provided by the present invention can withstand high temperature and high pressure at the same time, has good airtightness, and can be removed after use, and can well meet the performance requirements of vacuum forming of composite materials, with excellent comprehensive effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 The thermal weight loss curves of the sealing strips prepared in Example 2 and Comparative Example 1;
[0024] Figure 2 The scanning electron microscope images of the sealing strips prepared in Examples 2 to 4 and Comparative Examples 2 to 3;
[0025] Figure 3 These are actual application and measurement diagrams of the sealing strips prepared in Example 2, Example 4 and Comparative Example 1. DETAILED DESCRIPTION
[0026] The invention provides a sealing rubber strip, which is prepared from the following raw materials in parts by weight: 60-80 parts of synthetic rubber, 15-20 parts of natural rubber, 5-7 parts of coumarone resin, 5-15 parts of phenolic resin, 50-80 parts of filler, 1-5 parts of POSS modified glass microspheres, 1-5 parts of expandable microspheres, 10-50 parts of tackifiers, 1-10 parts of zinc oxide, 0.5-5 parts of stearic acid, 0.1-5 parts of color powder and 0.1-2 parts of antioxidant.
[0027] Calculated by weight, the raw materials of the sealing strip provided by the present invention include 60 to 80 parts of synthetic rubber, specifically 62 parts, 65 parts, 70 parts, 75 parts or 78 parts.
[0028] In the present invention, the synthetic rubber preferably includes one or more of butyl rubber, chlorinated butyl rubber, brominated butyl rubber, nitrile rubber, chloroprene rubber, ethylene propylene rubber and EPDM rubber; the chlorinated butyl rubber is preferably chlorinated butyl rubber 1066; the brominated butyl rubber is preferably brominated butyl rubber 2222; the EPDM rubber is preferably EPDM rubber 4045.
[0029] Calculated by weight, the raw materials of the sealing strip provided by the present invention include 15 to 20 parts of natural rubber, specifically 16 parts, 17 parts, 18 parts or 19 parts.
[0030] In terms of mass fraction, the raw material of the sealing strip provided by the present invention includes 5 to 7 parts of coumarone resin, specifically 6 parts.
[0031] Calculated by weight, the raw materials of the sealing strip provided by the present invention include 5 to 15 parts of phenolic resin, specifically 7 parts, 9 parts, 11 parts or 13 parts.
[0032] In parts by mass, the raw materials of the sealing strip provided by the present invention include 50 to 80 parts of filler, specifically 52 parts, 55 parts, 58 parts, 60 parts, 65 parts, 70 parts, 75 parts or 78 parts.
[0033] In the present invention, the filler preferably includes one or more of silicon dioxide, calcium carbonate, talc, kaolin and clay.
[0034] In the present invention, the particle size of the filler is preferably 400-1000 mesh, specifically 500 mesh, 600 mesh, 700 mesh, 800 mesh or 900 mesh.
[0035] In terms of mass fraction, the raw materials of the sealing adhesive strip provided by the present invention include 1 to 5 parts of POSS modified glass microspheres, specifically 2 parts, 3 parts or 4 parts.
[0036] In the present invention, the POSS modified glass microspheres are preferably POSS modified hollow glass microspheres; the particle size of the POSS modified glass microspheres is preferably not more than 30 μm, specifically 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm or 30 μm, and the wall thickness is preferably 1.5 to 3.5 μm, specifically 2 μm, 2.5 μm or 3 μm.
[0037] Calculated by weight, the raw materials of the sealing strip provided by the present invention include 1 to 5 parts of expandable microspheres, specifically 2 parts, 3 parts or 4 parts.
[0038] In the present invention, the expandable microspheres preferably include one or more of thermoplastic polyurethane (TPU), thermoplastic rubber (TPR) and polyvinyl chloride (PVC).
[0039] In parts by mass, the raw materials of the sealing strip provided by the present invention include 10 to 50 parts of tackifier, specifically 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts or 45 parts.
[0040] In the present invention, the tackifier is preferably polyisobutylene.
[0041] Calculated by weight, the raw materials of the sealing strip provided by the present invention include 1 to 10 parts of zinc oxide, specifically 2 parts, 4 parts, 6 parts or 8 parts.
[0042] In parts by mass, the raw materials of the sealing strip provided by the present invention include 0.5 to 5 parts of stearic acid, specifically 0.8 parts, 1 parts, 2 parts, 3 parts, 4 parts or 4.5 parts.
[0043] In parts by mass, the raw materials of the sealing strip provided by the present invention include 0.1 to 5 parts of color powder, specifically 0.5 parts, 1 parts, 2 parts, 3 parts, 4 parts or 4.5 parts.
[0044] In the present invention, the toner preferably includes phthalocyanine green.
[0045] Calculated by weight, the raw materials of the sealing strip provided by the present invention include 0.1 to 2 parts of antioxidant, specifically 0.5 parts, 1 part, 1.2 parts, 1.5 parts or 1.8 parts.
[0046] In the present invention, the antioxidant preferably includes one or more of an amine antioxidant, a phenol antioxidant and an organic sulfide antioxidant; the amine antioxidant preferably includes one or more of an RD antioxidant, a DPPD antioxidant, an AW antioxidant, a MC antioxidant and a 4010 antioxidant; the phenol antioxidant preferably includes catechol; and the organic sulfide antioxidant preferably includes dithiocarbamate.
[0047] The sealing strip provided by the present invention has a strong shape-keeping ability under high temperature and high pressure and will not be collapsed to cause air leakage; the addition of POSS modified glass has a higher degree of cross-linking and better temperature resistance; the product has high cohesion and basically no peeling residue.
[0048] The present invention also provides a method for preparing the sealing strip described in the above scheme, comprising the following steps:
[0049] (1) Plasticizing synthetic rubber and natural rubber and then discharging them to obtain premixed rubber;
[0050] (2) The premixed rubber is mixed with coumarone resin, phenolic resin, filler, POSS modified glass microspheres, expandable microspheres, tackifier, zinc oxide, stearic acid, toner and antioxidant in sequence, allowed to stand and extruded to obtain the sealing strip.
[0051] The present invention plasticizes synthetic rubber and natural rubber and then feeds them to obtain premixed rubber. In the present invention, the plasticizing temperature is preferably 30-50°C, specifically 30°C, 35°C, 40°C, 45°C or 50°C, the roller distance is preferably 50-800μm, specifically 50μm, 100μm, 150μm, 200μm, 300μm, 500μm, 700μm or 800μm, the speed ratio is preferably 1:1.2-1.3, specifically 1:1.2, 1:1.22, 1:1.24, 1:1.27 or 1:1.3; the plasticizing is preferably stopped after 10 thin passes; the plasticizing equipment is preferably an open mill with a cooling function.
[0052] After obtaining the premixed rubber, the present invention sequentially mixes, leaves and extrudes the premixed rubber with coumarone resin, phenolic resin, filler, POSS modified glass microsphere, expandable microsphere, tackifier, zinc oxide, stearic acid, toner and antioxidant to obtain the sealing strip. In the present invention, the preparation method of the POSS modified glass microsphere is preferably: glass microsphere, alkali and water are mixed (denoted as mixing A) to carry out hydroxylation to obtain hydroxylated glass microsphere, the hydroxylated glass microsphere is mixed with alcohol and coupling agent (denoted as mixing B) to carry out mercapto reaction to obtain mercaptolated glass microsphere, the mercaptolated glass microsphere is mixed with vinyl-cage polysilsesquioxane (vinyl-POSS), photoinitiator and tetrahydrofuran (denoted as mixing C) to carry out ultraviolet light reaction.
[0053] In the present invention, the glass microspheres are preferably hollow glass microspheres; the particle size of the glass microspheres is preferably not more than 30 μm, specifically 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm or 30 μm, and the wall thickness is preferably 1.5 to 3.5 μm, specifically 2 μm, 2.5 μm or 3 μm.
[0054] In the present invention, the alkali is preferably sodium hydroxide; and the mass ratio of the glass microspheres to the alkali is preferably 100:8.
[0055] In the present invention, the mass ratio of the alkali to water is preferably 1:80-120, specifically 1:80, 1:90, 1:100, 1:110 or 1:120.
[0056] In the present invention, the mixing A is preferably: ultrasonically dispersing glass microspheres in alkali and water.
[0057] In the present invention, the hydroxylation reaction is preferably carried out in a reflux state; the hydroxylation reaction is preferably carried out under stirring conditions; the insulation reaction time of the hydroxylation reaction is preferably 15 to 60 minutes, specifically 15 minutes, 25 minutes, 30 minutes, 35 minutes, 45 minutes or 60 minutes.
[0058] In the present invention, the hydroxylation reaction preferably further includes washing the obtained product (referred to as the first washing) and then drying (referred to as the first drying); the reagent used for the first washing is preferably deionized water; the temperature for the first drying is preferably 50-80°C, and the heat preservation and drying time is preferably 12h.
[0059] In the present invention, the alcohol is preferably ethanol; the mass ratio of the hydroxylated glass microspheres to the alcohol is preferably 1:5-15, specifically 1:5, 1:7, 1:10, 1:12 or 1:15.
[0060] In the present invention, the coupling agent preferably includes KH580; the mass ratio of the hydroxylated glass microspheres to the coupling agent is preferably 1:3-10, specifically 1:3, 1:5, 1:7, 1:9 or 1:10.
[0061] In the present invention, the mixture B is preferably: dispersing hydroxylated glass microspheres in alcohol, and then adding a coupling agent to the resulting mixed solution and stirring.
[0062] In the present invention, the temperature of the thiolation reaction is preferably 10-30° C., specifically 25° C., and the insulation reaction time is preferably 0.5-2 h, specifically 1 h.
[0063] In the present invention, after the thiolation reaction, the product is preferably washed (referred to as the second washing) and then dried (referred to as the second drying); the reagent used for the second washing is preferably deionized water; the temperature of the second drying is preferably 50-80° C., and the heat preservation and drying time is preferably 12 hours.
[0064] In the present invention, the mass ratio of the mercaptolated glass microspheres to the vinyl-POSS is preferably 1:1-3, specifically 1:1, 5:8, 1:2 or 1:3.
[0065] In the present invention, the photoinitiator preferably includes 184 initiator; the mass ratio of the thiolated glass microspheres to the photoinitiator is preferably 3 to 5:1, specifically 4:1 or 5:1.
[0066] In the present invention, the mass ratio of the mercaptolated glass microspheres to tetrahydrofuran is preferably 1:3-5, specifically 1:4. The present invention uses tetrahydrofuran as a solvent, which has good dispersibility.
[0067] In the present invention, the mixing C is preferably stirring mixing.
[0068] In the present invention, the temperature of the ultraviolet light reaction is preferably 10-30° C., specifically 25° C., and the insulation reaction time is preferably 0.5-2 h, specifically 1 h.
[0069] In the present invention, after the ultraviolet light reaction, it is preferred that the product obtained is sequentially subjected to rotary evaporation, washing (referred to as the third washing) and drying (referred to as the third drying); the temperature of the rotary evaporation is preferably 50-80°C, specifically 60°C, and the insulation rotary evaporation time is preferably 0.5-2h, specifically 1h; the reagent used for the third washing is preferably deionized water; the temperature of the third drying is preferably 50-80°C, specifically 60°C, and the insulation rotary evaporation time is preferably 0.5-2h, specifically 1h.
[0070] In the present invention, the mixing is preferably: the premixed rubber is first mixed with filler, coumarone resin, tackifier, stearic acid, zinc oxide and toner, and then the obtained mixture is secondly mixed with POSS modified glass microspheres, expandable microspheres, antioxidant and phenolic resin.
[0071] In the present invention, the first mixing temperature is preferably 80-120°C, specifically 100°C, and the mixing time is preferably 20 min; the second mixing temperature is 40-60°C, specifically 50°C, and the mixing time is preferably 5 min.
[0072] In the present invention, the standing time is preferably 8 to 12 hours, specifically 9 hours, 10 hours or 11 hours.
[0073] In the present invention, the extrusion molding equipment is preferably a screw extruder.
[0074] The present invention also provides the use of the sealing strip described in the above scheme or the sealing strip obtained by the preparation method described in the above scheme in vacuum forming of composite materials.
[0075] The sealing strip provided by the present invention can withstand high temperature and high pressure at the same time, has good air tightness, can be removed after use, can well meet the performance requirements of composite material vacuum forming, and has excellent comprehensive effect.
[0076] In order to further illustrate the present invention, the scheme of the present invention is described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be understood as limiting the protection scope of the present invention.
[0077] Example 1
[0078] (1) 10 parts of hollow glass microspheres with a particle size of less than 30 μm and a wall thickness of 1.5 to 3.5 μm were selected, ultrasonically dispersed in 80 parts of a 10 g / L sodium hydroxide aqueous solution, stirred under reflux for 30 min, washed, and dried to obtain hydroxylated glass microspheres.
[0079] (2) Dispersing 10 parts of hydroxylated glass microspheres in 100 parts of ethanol solution, adding 50 parts of KH580, stirring for 1 hour, washing, and drying to obtain thiolated glass microspheres.
[0080] (3) 10 parts of thiolated glass microspheres, 16 parts of vinyl-POSS, and 2 parts of photoinitiator (184 initiator) are added to 40 parts of tetrahydrofuran in sequence, stirred evenly, reacted with ultraviolet light, rotary evaporated, washed, and dried to obtain POSS-modified glass microspheres.
[0081] Example 2
[0082] The sealing strip prepared in this embodiment is made of the following raw materials in terms of weight:
[0083] 60 parts of chlorinated butyl rubber 1066 (JSR), 20 parts of natural rubber, 50 parts of calcium carbonate (400 mesh), 30 parts of clay (1000 mesh), 5 parts of coumarone resin, 2 parts of POSS modified glass microspheres (prepared in Example 1), 3 parts of expandable microspheres, 40 parts of polyisobutylene tackifier, 1 part of stearic acid, 3 parts of zinc oxide, 0.5 parts of toner, 2 parts of MC antioxidant and 10 parts of phenolic resin.
[0084] The invention discloses a method for preparing a mixed rubber by using an open mill with a cooling function, firstly plasticizing the chlorobutyl rubber and the natural rubber, and then discharging the mixed rubber after 10 thin passes; mixing the mixed rubber with calcium carbonate, clay, coumarone resin, polyisobutylene tackifier, stearic acid and color powder for 20 minutes; then adding POSS modified glass microspheres, expandable microspheres, MC antioxidant and phenolic resin for mixing for 5 minutes, standing for 10 hours, and then extruding the mixed rubber into strips by using an extruder, and then winding and packing the strips.
[0085] Example 3
[0086] The sealing strip prepared in this embodiment is made of the following raw materials in terms of weight:
[0087] 222240 parts of brominated butyl rubber, 404520 parts of EPDM rubber, 20 parts of natural rubber, 30 parts of calcium carbonate (400 mesh), 50 parts of talc (800 mesh), 3 parts of coumarone resin, 1 part of POSS modified glass microspheres (prepared in Example 1), 4 parts of expandable microspheres, 40 parts of polyisobutylene tackifier, 1 part of stearic acid, 3 parts of zinc oxide, 0.5 parts of toner, 1 part of RD antioxidant and 8 parts of phenolic resin.
[0088] The invention discloses a method for preparing a mixed rubber by using an open mill with a cooling function, firstly plasticizing brominated butyl rubber, EPDM rubber and natural rubber, and then discharging the mixed rubber after 10 thin passes, and mixing the mixed rubber with calcium carbonate, talcum powder, coumarone resin, polyisobutylene tackifier, stearic acid and color powder for 20 minutes, then adding POSS modified glass microspheres, expandable microspheres, RD antioxidant and phenolic resin for 5 minutes, standing for 10 hours, and then extruding the mixed rubber into strips by using an extruder, and then winding and packing the strips.
[0089] Example 4
[0090] The sealing strip prepared in this embodiment is made of the following raw materials in terms of weight:
[0091] 40 parts of chlorinated butyl rubber 1066 (JSR), 20 parts of EPDM 4045, 20 parts of natural rubber, 50 parts of calcium carbonate (400 mesh), 30 parts of clay (1000 mesh), 3 parts of coumarone resin, 4 parts of POSS modified glass microspheres (prepared in Example 1), 1 part of expandable microspheres, 50 parts of polyisobutylene tackifier, 1 part of stearic acid, 3 parts of zinc oxide, 0.5 parts of toner, 1 part of AW antioxidant and 10 parts of phenolic resin.
[0092] The invention discloses a method for preparing a mixed rubber by using an open mill with a cooling function, firstly plasticizing chlorobutyl rubber, EPDM rubber and natural rubber, and then discharging the mixed rubber after 10 thin passes; mixing the mixed rubber with calcium carbonate, clay, coumarone resin, polyisobutylene tackifier, stearic acid and color powder for 20 minutes; then adding POSS modified glass microspheres, expandable microspheres, AW antioxidant and phenolic resin for mixing for 5 minutes, standing for 10 hours, and then extruding the mixed rubber into strips by using an extruder, and then winding and packing the strips.
[0093] Comparative Example 1
[0094] The sealing strip prepared in this comparative example is made of the following raw materials in parts by mass:
[0095] 222240 parts of brominated butyl rubber, 404520 parts of EPDM rubber, 20 parts of natural rubber, 30 parts of calcium carbonate (400 mesh), 50 parts of talc (800 mesh), 3 parts of coumarone resin, 40 parts of polyisobutylene tackifier, 1 part of stearic acid, 3 parts of zinc oxide, 0.5 parts of color powder, 1 part of RD antioxidant and 8 parts of phenolic resin.
[0096] The invention discloses a method for preparing a mixed rubber by using an open mill with a cooling function, firstly plasticizing brominated butyl rubber, EPDM rubber and natural rubber, and then discharging the mixed rubber after 10 thin passes, and mixing the mixed rubber with calcium carbonate, talcum powder, coumarone resin, polyisobutylene tackifier, stearic acid and color powder for 20 minutes, then adding POSS-modified glass microspheres, expandable microspheres, RD antioxidant and phenolic resin for 5 minutes, standing for 10 hours, and then extruding the mixed rubber into strips by using an extruder, and then winding and packing the strips.
[0097] Comparative Example 2
[0098] The sealing strip prepared in this comparative example is made of the following raw materials in parts by mass:
[0099] 222240 parts of brominated butyl rubber, 404520 parts of EPDM rubber, 20 parts of natural rubber, 30 parts of calcium carbonate (400 mesh), 50 parts of talc (800 mesh), 3 parts of coumarone resin, 2 parts of POSS modified glass microspheres (prepared in Example 1), 40 parts of polyisobutylene tackifier, 1 part of stearic acid, 3 parts of zinc oxide, 0.5 parts of toner, 1 part of RD antioxidant and 8 parts of phenolic resin.
[0100] The invention discloses a method for preparing a mixed rubber by using an open mill with a cooling function, firstly plasticizing brominated butyl rubber, EPDM rubber and natural rubber, and then discharging the mixed rubber after 10 thin passes, and mixing the mixed rubber with calcium carbonate, talcum powder, coumarone resin, polyisobutylene tackifier, stearic acid and color powder for 20 minutes, then adding POSS-modified glass microspheres, expandable microspheres, RD antioxidant and phenolic resin for 5 minutes, standing for 10 hours, and then extruding the mixed rubber into strips by using an extruder, and then winding and packing the strips.
[0101] Comparative Example 3
[0102] The sealing strip prepared in this comparative example is made of the following raw materials in parts by mass:
[0103] 40 parts of chlorinated butyl rubber 1066 (JSR), 20 parts of EPDM 4045, 20 parts of natural rubber, 30 parts of calcium carbonate (400 mesh), 50 parts of clay (1000 mesh), 3 parts of coumarone resin, 3 parts of expandable microspheres, 50 parts of polyisobutylene tackifier, 1 part of stearic acid, 3 parts of zinc oxide, 0.5 parts of toner, 1 part of AW antioxidant and 10 parts of phenolic resin.
[0104] Using an open mill with a cooling function, chlorobutyl rubber, EPDM rubber and natural rubber are first plasticized, and the mixed rubber is obtained after 10 thin passes; the mixed rubber is mixed with calcium carbonate, clay, coumarone resin, polyisobutylene tackifier, stearic acid and color powder for 20 minutes; then expandable microspheres, AW antioxidant and phenolic resin are added and mixed for 5 minutes. After standing for 10 hours, the mixed rubber is extruded into strips by an extruder, and rolled and packed.
[0105] Test Example 1
[0106] The sealing strips prepared in Example 2 and Comparative Example 1 were subjected to a thermal gravimetric test. The results are as follows: Figure 1 As shown. Figure 1 It can be seen that the glass microspheres modified by POSS significantly improve the bonding strength between rubber and rubber, between fillers and between rubber and fillers. In the 230°C insulation section, the formula mass percentage of the unmodified glass microspheres gradually decreased from 100% to 94%, while the formula mass percentage of the POSS-modified glass microspheres decreased from 100% to only 99% due to the stronger intermolecular bonding force and fewer small molecules, which is a significant improvement.
[0107] Test Example 2
[0108] The sealing strips prepared in Examples 2 to 4 and Comparative Examples 2 to 3 were analyzed by scanning electron microscope. Figure 2 As shown. Figure 2 It can be seen that according to the room temperature and high temperature conditions of Comparative Example 2, only glass microspheres are added, and because of their small particle size, they are completely wrapped by the rubber and cannot play a supporting role in shape; according to the room temperature and high temperature conditions of Comparative Example 3, only expandable microspheres are added, but no expandable microspheres with large particle sizes are observed after high temperature, which may be due to external extrusion, the microspheres are broken, and ultimately cannot play a supporting role; According to Examples 2 to 4, it can be seen that the particles are large and small, the large ones are expandable microspheres, and the small ones are glass microspheres; after the expandable microspheres expand, the small glass microspheres support them and are not easily flattened; at the same time, in a microscopic state, the small glass microspheres and the large expandable microspheres together effectively fill the pores in the rubber, and the macroscopic effect is reflected in that the shape of the sealing strip is well maintained.
[0109] Test Example 3
[0110] The sealing strips prepared in Example 2, Example 4 and Comparative Example 1 were actually applied and measured, and the results are as follows: Figure 3 As shown. Figure 3It can be seen that from the actual application of the autoclave, Comparative Example 1 underwent severe deformation under a pressure of 2 MPa, and the thickness dropped from the original 3 mm to 1.41 mm, with a thickness retention rate of 47%. After adding expandable microspheres and POSS modified glass microspheres, it can have a certain pressure-bearing effect under a pressure of 2 MPa, among which Example 2 performed the best, with a thickness retention rate of 85.3%.
[0111] It can be seen from the above embodiments that the sealing strip provided by the present invention can withstand high temperature and high pressure at the same time, has good airtightness, and can be removed after use. It can well meet the performance requirements of composite material vacuum forming and has excellent comprehensive effect.
[0112] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A sealing strip, characterized in that: The invention comprises the following raw materials in parts by weight: 60-80 parts of synthetic rubber, 15-20 parts of natural rubber, 5-7 parts of coumarone resin, 5-15 parts of phenolic resin, 50-80 parts of filler, 1-5 parts of POSS modified glass microspheres, 1-5 parts of expandable microspheres, 10-50 parts of tackifier, 1-10 parts of zinc oxide, 0.5-5 parts of stearic acid, 0.1-5 parts of color powder and 0.1-2 parts of antioxidant.
2. The sealing strip according to claim 1, characterized in that: The synthetic rubber includes one or more of butyl rubber, chlorinated butyl rubber, brominated butyl rubber, nitrile rubber, chloroprene rubber, ethylene propylene rubber and ethylene propylene diene monomer rubber.
3. The sealing strip according to claim 1 or 2, characterized in that: The particle size of the filler is 400-1000 meshes.
4. The sealing strip according to claim 1, characterized in that: The POSS modified glass microspheres are POSS modified hollow glass microspheres; The particle size of the POSS modified glass microspheres does not exceed 30 μm, and the wall thickness is 1.5 to 3.5 μm.
5. The sealing strip according to claim 1 or 4, characterized in that: The expandable microspheres include one or more of thermoplastic polyurethane, thermoplastic rubber and polyvinyl chloride.
6. The sealing strip according to claim 1, characterized in that: The antioxidant includes one or more of amine antioxidants, phenol antioxidants and organic sulfide antioxidants.
7. The method for preparing the sealing strip according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) Plasticizing synthetic rubber and natural rubber and then discharging them to obtain premixed rubber; (2) The premixed rubber is mixed with coumarone resin, phenolic resin, filler, POSS modified glass microspheres, expandable microspheres, tackifier, zinc oxide, stearic acid, toner and antioxidant in sequence, allowed to stand and extruded to obtain the sealing strip.
8. The preparation method according to claim 7, characterized in that: The preparation method of the POSS modified glass microspheres comprises: mixing glass microspheres, alkali and water to carry out hydroxylation reaction to obtain hydroxylated glass microspheres, mixing the hydroxylated glass microspheres with alcohol and a coupling agent to carry out thiol reaction to obtain thiolated glass microspheres, and mixing the thiolated glass microspheres with vinyl-cage polysilsesquioxane, a photoinitiator and tetrahydrofuran to carry out ultraviolet light reaction.
9. The preparation method according to claim 7 or 8, characterized in that: The temperature of the plasticizing is 30-50° C., the roller distance is 50-800 μm, and the speed ratio is 1:1.2-1.3; the plasticizing is stopped after the thin pass is 10 times.
10. Use of the sealing strip according to any one of claims 1 to 6 or the sealing strip obtained by the preparation method according to any one of claims 7 to 9 in vacuum forming of composite materials.